A Longitudinal study of organizational capability development process : rendering project portfolio management capability (PPMC) - Butt, Aurangzeab Farid (Vaasan yliopisto, 2018)
This dissertation analyzes the heterogeneous development paths of project portfolio management capability (PPMC). Earlier, modern literature has prioritized its focus on the performance-based classification of organizational capabilities, while their development process remained obscure. Consequently, scholarship advocating high performance organizational capabilities (such as a dynamic capability) are in abundance. However, the evidence of development path-affected performance dissimilarities is rather sparse or otherwise remained implicit due to the increasing conceptual differences among the prominent scholarship. Along with the longitudinal process research design of this research, a critical realism-based retroduction approach has enabled the discovery of the capability investigation framework. This capability dimensions, routines, and performance outcome based framework has been further extended to investigate project portfolio management capability (PPMC). This retroductive framework is operationalized to evidence the nine years of capability development path heterogeneity at three entities of a case company. The research case findings explain the effect of underlying mechanisms, which due to their context dependent outcomes, either positively reinforce the existing development paths or lead to an alternative path selection. The case findings also confirm that higher performance is not universally attributable to any specific organizational capability known in the literature. Instead, the actuation of all three identified learning mechanisms (of a learning organization) can develop high performing organizational capabilities. This research concludes that a capability development process endures through an extemporized mixture of refinement, reconfiguration, and transformation activities. As a result, an organizational capability always remains idiosyncratic in its details and, hence, produce diverse performance outcomes. Finally, this PhD research has created a critical realist model to extend the emergent theory of capability path dependence to the other organizational contexts.

Tämä tutkimus analysoi projektiportfolion hallintaa koskevan kyvykkyyden moninaisia kehittämisvaihtoehtoja. Aiempi tutkimus on keskittynyt organisaation toimintaa tukevien kyvykkyyksien luokitteluun, mutta kyvykkyyksien kehittymistä on tutkittu vähemmän. Kyvykkyyden kehittymiseen (kuten dynaamiseen kyvykkyyteen) tähtäävä tutkimus keskittyy enimmäkseen organisaation näkökulmaan. Lisäksi kyvykkyyden kehittymistutkimusta vaikeuttaa se, että alan keskeiset tutkijat käyttävät keskenään erilaista terminologiaa. Tämä tutkimus on pitkittäinen ja siinä rakennettiin kriittisen realismin lähestymistavan avulla kyvykkyyden kehittymisen tutkimista varten viitekehys. Kyvykkyyden osatekijöitä, rutiineja ja toiminnan tuloksia kuvaavaa viitekehystä kehitettiin edelleen niin, että sitä voidaan käyttää organisaation projektisalkun hallinnan kyvyn selvittämiseen. Tämän viitekehyksen avulla osoitettiin tapausyrityksen kolmen yksikön kyvykkyyden kehittymispolku yhdeksän vuoden ajalta. Tapaustutkimuksen tulokset selittävät kyvykkyyden kehittymisen mekanismeja, jotka joko vahvistavat organisaation vallitsevia kehittymispolkuja tai johtavat uuden kehittymispolun valintaan. Tapaustutkimukset myös osoittavat, että tehokas toiminta ei ole kirjallisuudessa mainitun yksittäisen organisaation kyvykkyysosatekijän seurausta. Sen sijaan kaikki tunnistetut oppivan organisaation oppimiskeinot kehittävät tehokkaasti toimivan organisaation kyvykkyyksiä. Tämän tutkimuksen johtopäätös on, että kyvykkyyden kehittymisprosessi muodostuu improvisoiduista hienosäätö-, uudelleenkonfigurointi- ja muokkausvaiheista. Niiden tuloksena organisaation kyvykkyys säilyy aina yksityiskohdissaan omaperäisenä ja siten voi tuottaa vaihtelevia tuloksia. Tämä väitöskirja on luonut kriittiseen realismiin perustuvan mallin, jolla laajennetaan uutta kyvykkyyden kehittymispolkuriippuvuuden teoriaa muihin organisaatiokonteksteihin.
Keywords: oppiva organisaatio; kyvykkyys; fi=Tuotantotalous| sv=Produktionsekonomi| en=Industrial Management|